PECAM-1 and gelatinase B coexist in vascular cuffs of multiple sclerosis lesions - Nelissen, I.; Gveric, D.; Van Noort, J. M.; Cuzner, M. L.; Opdenakker, G. (Neuropathology and applied neurobiology, 2006)
In multiple sclerosis (MS), the matrix metalloprotease (MMP) gelatinase B/MMP‐9 and platelet endothelial cell adhesion molecule (PECAM)‐1 have both been implicated in trans‐endothelial infiltration of leucocytes into the brain, but their functional connection has not yet been investigated. We investigated the expression of gelatinase B and PECAM‐1 in  post mortem brains of MS patients by immunohistochemistry. Because increased soluble PECAM‐1 serum levels have been observed in MS patients, we also tested in vitro whether this could be due to cleavage of PECAM‐1 by gelatinase B or matrilysin‐1/MMP‐7. Constitutive expression of PECAM‐1 was found on brain endothelial cells, whilst in active MS lesions cell‐bound PECAM‐1 was highly up‐regulated on foamy macrophages in perivascular infiltrates and co‐localized with gelatinase B. However, human THP‐1 monocyte‐bound or soluble recombinant PECAM‐1 were both resistant to proteolytic cleavage by gelatinase B or matrilysin‐1 in vitro, as demonstrated by Western blot analysis and flow cytometry. These results suggest that PECAM‐1 and gelatinase B may complement each other during the transmigration of the blood–brain barrier by mononuclear cells.